Defensa legal de la reputación corporativa - Fernando Moreno Cea; Efrén Díaz Díaz (Church, Communication and Culture, 2020)
This study highlights the need to complement the necessary communication actions with other legal and procedural actions when the institutional confidence and the corporate reputation of an entity and its managers are affected. To this end, an analysis will be made of the actions carried out by the authors when dealing with a real case with a certain risk of breaking the institutional and reputational trust of a development cooperation entity related to a Catholic Church entity. The objective is to help understand, based on the case examined, the appropriateness of the measures to be adopted to achieve the effective defence of the institutional trust and corporate reputation damaged. Knowing the legal strategy applied will provide light on the opportunity to take legal action as a practical and effective means of achieving satisfactory solutions for entities and individuals affected, and have practical references to apply in similar situations to safeguard protected legal assets of a personal, institutional or corporate nature, such as honour, one's own image or good name. The conclusion is that "Communication 'and' Law" are complementary and necessary for the effective planning and defence of the corporate reputation of entities and managers.